Nietzsche in Hollywood : images of the Übermensch in early American cinema - Rukgaber, Matthew (State University of New York Press, 2022)
"Argues that Nietzsche's idea of the Übermensch was a central concern of filmmakers in the 1920s and 1930s"-- Provided by publisher.
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900 -- Influence.; Nietzsche, Friedrich Wilhelm, -- 1844-1900; Superman (Philosophical concept); Philosophy in motion pictures.; Motion pictures -- United States -- History -- 20th century.; Surhomme.; Philosophie au cinéma.; Cinéma -- États-Unis -- Histoire -- 20e siècle.; PERFORMING ARTS / Film & Video / History & Criticism.; Influence (Literary, artistic, etc.); Motion pictures; Philosophy in motion pictures; United States; 1900-1999; History